Exploring the most demanding scenarios in elite youth basketball: a comprehensive analysis across playing positions and time windows - Irid, Yannis; Hutin, Julian; Toussaint, Jean-François; Sedeaud, Adrien (Biology of Sport, 2025)
This study aimed to examine the Most Demanding Scenarios (MDS) in elite youth basketball players, focusing on position-specific differences across various time windows. Data were collected from 31 players (20 males, 11 females) across two seasons during 40 official games using a 20-Hz Local Positioning System and 100-Hz accelerometer. Metrics included total distance, high-speed running distance, accelerations, decelerations, jumps, and changes of direction. Peak Demands (PD), High-Intensity Periods (HIP), and Very High-Intensity Periods (VHIP) were calculated using rolling averages over 10, 30, 60, and 120-second windows. Mixed linear models compared PD across time intervals and between playing positions (frontcourt vs. backcourt). Shorter time windows showed higher relative peak values for both males and females. Relative distances declined with longer intervals, from 251.34±23.46 m·min −1 (10 s) to 113.61±13.52 m·min −1 (120 s) for males ( p < 0.001; d = 7.20, nearly perfect effect), and from 237.37±24.16 m·min −1 to 114.52±11.7 m·min −1 for females ( p < 0.001; d = 6.47, nearly perfect effect). Male backcourt players (BC) had higher PD than frontcourt players (FC) across most variables and windows, except for changes of direction. Female BC showed significantly higher PD in acceleration (10.26±2.28 m vs. 9.07±2.83 m; p = 0.04; d = -0.45, small effect) and deceleration distance (11.9±2.39 m vs. 10.12±3.9 m; p = 0.02; d = -0.53, small effect) over 120 s. Additionally, male FC were more frequently exposed to HIP over 10 s ( p = 0.011; d = 0.20, trivial effect) and VHIP over 30 s ( p = 0.001; d = 0.26, small effect) for distance covered, whereas female BC consistently demonstrated more frequent passages in VHIP for sprint durations across all time windows. These findings highlight significant position-specific differences in the MDS of elite youth basketball players. Understanding these demands emphasizes the need for tailored, position-specific training and conditioning programs to optimize performance.